2009
DOI: 10.1007/s10157-009-0156-8
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Asian Forum of Chronic Kidney Disease Initiative (AFCKDI) 2007. “Current status and perspective of CKD in Asia”: diversity and specificity among Asian countries

Abstract: The Japanese Society of Nephrology (JSN) sponsored the Asian Forum of CKD Initiative (AFCKDI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Asian studies done among general population had shown prevalence of CKD to be 3-5% in southern China, 13% in southern Taiwan, 9.2% in Japan and 5.2% in Indonesia. 24 The community in Delhi on the prevalence of low eGFR was 4.2%. 25 Study done by Weiping Jia among diabetic patients in China revealed a prevalence of 29.6% 26 and a global prevalence of 22% 27 for CKD.…”
Section: Discussionmentioning
confidence: 92%
“…Asian studies done among general population had shown prevalence of CKD to be 3-5% in southern China, 13% in southern Taiwan, 9.2% in Japan and 5.2% in Indonesia. 24 The community in Delhi on the prevalence of low eGFR was 4.2%. 25 Study done by Weiping Jia among diabetic patients in China revealed a prevalence of 29.6% 26 and a global prevalence of 22% 27 for CKD.…”
Section: Discussionmentioning
confidence: 92%
“…20 The large size of this study bestows high power to identify factors associated with renal death. Previous attempts to identify risk factors have been hampered by several issues, not the least the large number of renal events required to obtain reliable results and the low rate of reporting kidney disease as a cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…19 The high incidence and prevalence of kidney disease in the Asia-Pacific region has been identified as a major public health issue by the International Society of Nephrology, the Asian Pacific Society of Nephrology, and other groups. 20 To address this challenge, the Asian Forum of CKD Initiative (APFCKDI) was established in 2007, with the investigation of risk factors for kidney disease in the region as a major priority. Hence, the aim of the current study was to determine risk factors for renal death using data from Ͼ560 000 individuals from the Asia-Pacific region and, by doing so, to highlight possible future targets for intervention.…”
mentioning
confidence: 99%
“…On the contrary, however, some countries still lack almost everything necessary for the management of CKD, most notably the nephrologists. Therefore, one of the main purposes of the first meeting was to compile the present status of CKD in Asia, with regard to prevalence, regional problems, and future collaboration [7]. To what extent the estimated glomerular filtration rate (eGFR) should be modified to the need of the Asian population was enthusiastically discussed [6,8,10].…”
Section: Summary Of Previous Asian Forum Of Chronic Kidney Disease Inmentioning
confidence: 99%